Endothelial cell-fatty acid binding protein 4 promotes angiogenesis: role of stem cell factor/c-kit pathway - Elmasri, Harun (2012)
Fatty acid binding protein 4 (FABP4) plays an important role in regulation of glucose and lipid homeostasis as well as inflammation through its actions in adipocytes and macrophages. FABP4 is also expressed in a subset of endothelial cells, but its role in this cell type is not known. We found that FABP4-deficient human umbilical vein endothelial cells (HUVECs) demonstrate a markedly increased susceptibility to apoptosis as well as decreased migration and capillary network formation. Aortic rings from FABP4(−/−) mice demonstrated decreased angiogenic sprouting, which was recovered by reconstitution of FABP4. FABP4 was strongly regulated by mTORC1 and inhibited by Rapamycin. FABP4 modulated activation of several important signaling pathways in HUVECs, including downregulation of P38, eNOS, and stem cell factor (SCF)/c-kit signaling. Of these, the SCF/c-kit pathway was found to have a major role in attenuated angiogenic activity of FABP4-deficient ECs as provision of exogenous SCF resulted in a significant recovery in cell proliferation, survival, morphogenesis, and aortic ring sprouting. These data unravel a novel pro-angiogenic role for endothelial cell-FABP4 and suggest that it could be exploited as a potential target for diseases associated with pathological angiogenesis.